AMG, Inc. & Forsythe Solutions : lease vs. buy decisions - Jeffery, Mark, 1965- (SAGE Knowledge. Cases., 2006)
The AMG, Inc. and Forsythe Solutions case examines the lease versus buy decision for investments in technology. The case addresses issues pivotal to the investment decision such as varying the length of the lease, the useful life of the equipment, and alignment with the company's overall financial strategy. The scenario is for a real Fortune 500 global financial services firm that has been disguised for confidentiality reasons.This case illustrates the fundamentals of lease versus buy decisions in technology and how they differ from the typical capital equipment lease versus buy decision. Topics covered include depreciation and off-balance-sheet financing for a complex leasing scenario staggered in time across multiple business units.